Penerapan Model Make A Match Dalam Pembelajaran Mufradat Bahasa Arab Kelas VIIA di MTs Muhammadiyah 09 Purbalingga - Sekar Dwi Nur Aini; Nurfuadi Nurfuadi (Journal on Education, 2023)
In learning Arabic there are four abilities that must be learned and mastered by students, namely listening, speaking, reading and writing skills. To master these four skills, one of the efforts that must be taken is to increase the acquisition of mufradat or Arabic vocabulary, because this will greatly help the learning outcomes of the four Arabic language skills. In obtaining the mufradat, it is necessary to have an appropriate learning model so that students are able to properly absorb the mufrada conveyed by the teacher. One way is to use the Make A Match model which is a fun learning model in understanding mufradat. Based on the background that the author describes, the problem that the author choose to be the focus of this research, namely How to Apply the Make A Match Model in Learning Arabic Mufradat Class VIIA at MTs Muhammadiyah 09 Purbalingga. This study aims to find out and analyze how to apply the Make A Match model in learning Arabic mufradat at MTs Muhammadiyah 09 Purbalingga.This research is a type of field research (field research) which is descriptive qualitative in nature with data collection techniques through observation, interviews, and documentation. Then the data analysis that the author did through three stages, namely reduction, data presentation, and drawing conclusions.The results of this study indicate that mufrodat learning at MTs Muhammadiyah 09 Purbalingga, teachers carry out learning in three stages, namely the preparation, implementation and evaluation stages. Then in carrying out mufradat learning the teacher uses the Make A Match model to help students understand and memorize the given mufradat. By using this model, create a fun learning atmosphere and make students more active when participating in learning activities.